Changes in plasma and urine metabolites associated with empagliflozin in patients with type 1 diabetes. Issue 11 (28th July 2021) - Liu, Hongyan; Sridhar, Vikas S.; Montemayor, Daniel; Lovblom, Leif Erik; Lytvyn, Yuliya; Ye, Hongping; Kim, Jiwan; Ali, Mir Tariq; Scarr, Daniel; Lawler, Patrick R.; Perkins, Bruce A.; Sharma, Kumar; et al.
Abstract: Aim: To examine the impact of the sodium‐glucose co‐transporter‐2 inhibitor, empagliflozin, on plasma and urine metabolites in participants with type 1 diabetes. Material and Methods: Participants (n = 40, 50% male, mean age 24.3 years) with type 1 diabetes and without overt evidence of diabetic kidney disease had baseline assessments performed under clamped euglycaemia and hyperglycaemia, on two consecutive days. Participants then proceeded to an 8‐week, open‐label treatment period with empagliflozin 25 mg/day, followed by repeat assessments under clamped euglycaemia and hyperglycaemia. Plasma and urine metabolites were first grouped into metabolic pathways using MetaboAnalyst software. Principal component analysis was performed to create a representative value for each sufficiently represented metabolic group (false discovery rate ≤ 0.1) for further analysis. Results: Of the plasma metabolite groups, tricarboxylic acid (TCA) cycle ( P  < .0001), biosynthesis of unsaturated fatty acids ( P  = .0045), butanoate ( P  < .0001), propanoate ( P  = .0053), and alanine, aspartate and glutamate ( P  < .0050) metabolites were increased after empagliflozin treatment under clamped euglycaemia. Of the urine metabolite groups, only butanoate metabolites ( P  = .0005) were significantly increased. Empagliflozin treatment also attenuated the increase in a number of urine metabolites observed with acute hyperglycaemia. Conclusions: Empagliflozin was associated with increased lipid and TCA cycle metabolites in participants with type 1 diabetes, suggesting a shift in metabolic substrate use and improved mitochondrial function. These effects result in more efficient energy production and may contribute to end‐organ protection by alleviating local hypoxia and oxidative stress.